Nitrogen-Doped CuO@CuS Core–Shell Structure for Highly Efficient Catalytic OER Application - Abu Talha Aqueel Ahmed; Abu Saad Ansari; Vijaya Gopalan Sree; Atanu Jana; Abhishek Meena; Sankar Sekar; Sangeun Cho; Hyungsang Kim; Hyunsik Im (Nanomaterials, 2023)
Water electrolysis is a highly efficient route to produce ideally clean H2 fuel with excellent energy conversion efficiency and high gravimetric energy density, without producing carbon traces, unlike steam methane reforming, and it resolves the issues of environmental contamination via replacing the conventional fossil fuel. Particular importance lies in the advancement of highly effective non-precious catalysts for the oxygen evolution reaction (OER). The electrocatalytic activity of an active catalyst mainly depends on the material conductivity, accessible catalytically active sites, and intrinsic OER reaction kinetics, which can be tuned via introducing N heteroatoms in the catalyst structure. Herein, the efficacious nitrogenation of CuS was accomplished, synthesized using a hydrothermal procedure, and characterized for its electrocatalytic activity towards OER. The nitrogen-doped CuO@CuS (N,CuO@CuS) electrocatalyst exhibited superior OER activity compared to pristine CuS (268 and 602 mV), achieving a low overpotential of 240 and 392 mV at a current density of 10 and 100 mA/cm2, respectively, ascribed to the favorable electronic structural modification triggered by nitrogen incorporation. The N,CuO@CuS also exhibits excellent endurance under varied current rates and a static potential response over 25 h with stability measured at 10 and 100 mA/cm2.